Penal and Non-Penal Approaches to the Legal Enforcement of Child Marriage: A Political Analysis of Criminal Law - Ismawati, Sri (International Journal of Criminology and Sociology, 2021)
This study is directed to examine the issue of child marriage from the perspective of criminal politics. Criminal political perspective child marriage is a perspective that not only sees the problem of child marriage solely as a matter of criminal law, but also tries to look at the problem of child marriage from a non-legal perspective. By using normative and juridical approach, the results showed that the perspective of politics of criminal law of child marriage is to see the problem of child marriage solely as a matter of criminal law, but also tries to look at the problem of child marriage from a non-legal perspective. The politics of criminal law with a penal approach can be done by using integrative formulation, revision, criminalization, penalization of child marriage, law enforcement against criminal acts related to child marriage, encouraging the making of Regional Regulations, Governor Regulations or Regulations of Regents. On other hand, the non-penal approach is by empowering the role of parents by conducting education, education and self-esteem; empowering the role of religious leaders, community leaders, traditional leaders; family economic empowerment, education empowerment and integral policy models